Latin American Disintegration under Jair Bolsonaro During Brazilian Chancellor Ernesto Araujo’s Mandate, 2019-2021 - Ana Livia Esteves (Vestnik RUDN. International Relations)
The article investigates the impact of Jair Bolsonaro’s foreign policy on Latin American integration during the mandate of his first chancellor, Ernesto Araujo, from January, 2019 to March, 2021. The research posits that the deterioration of Brazil’s bilateral relations with Argentina and Venezuela during this period was the main obstacle to the further development of Latin American integration, in accordance with the axis theory of regional integration proposed by Brazilian scholars Raquel Patricio and Amado Cervo. The focus of Araujo’s foreign policy on isolating Venezuela from regional initiatives was the main driver behind the decline of the Union of South American Nations (UNASUR) and the Community of Latin American and Caribbean States (CELAC). Brazil’s approach to the Venezuelan issue determined its engagement with the Forum for the Progress and Integration of South America (PROSUR), an institution that ultimately failed to deliver concrete results in democracy promotion and regional policy coordination. Brazil’s relations with the Southern Common Market (MERCOSUR) will be scrutinized in greater detail, given the organization’s institutional complexity and importance for Brasilia’s regional engagement. Furthermore, the research will attest to the deterioration of Brazil’s regional leadership and the strengthening of the role of countries such as Chile, Colombia and Peru. The author concludes that Ernesto Araujo’s policies have contributed to Latin American disintegration, for by the end of his term at the Brazilian Minister of Foreign Affairs, no institution at the Latin American level had the necessary instruments to promote economic, social or political coordination among the countries of the region.